A STUDY ON GOLD AS A SAFER INVESTMENT ALTERNATIVE AMONG SMALL AND MEDIUM INVESTORS WITH SPECIAL REFERENCE TO KOZHIKODE DISTRICT - Shobha (International Journal of Research -GRANTHAALAYAH, 2017)
Among the various precious metals “Gold” is the most popular as an investment. Why it is so? The answer is it is a mainstream asset as it is not only an effective diversifier but also gives a competitive return when compared to major financial assets. The present study analyses ‘Gold as a safer investment alternative’ by examining its risk and return in terms of other investment alternatives like stock and bond. The risk and return analysis of an asset class is better studied with its volatility measurement. The present study uses daily prices of gold, stock Nifty 5o, and India Government Bond. To measure the volatility of time series, Generalized autoregressive Conditional Heteroskedasticity GARCH(1,1) process is used the results shows that risk in terms of volatility of gold prices is 0.970124(<1) which showed less when compared to stock(is 0.956541(<1) and bond(1.003183(>1) risk. This study also analyses various demographical factors that influence on the decision to invest in gold and as well as in selecting a particular kind of gold investment. The chi-square test was applied and the results showed that all the variables under study except education qualification (‘p’ value 0.8308) dictated investors decision in selecting gold as an investment opportunity.